The Effect of Objective and Subjective Financial Literacy on Risky Credit Behavior Moderated by Financial Self-efficacy - Dea Amanda Putri; Erna Sulistyowati; Sofie Yunida Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study seeks to investigate the impact of both objective and perceived financial knowledge on high-risk credit behaviors among accounting students in Surabaya, with confidence in managing finances serving as a mediator. Utilizing Structural Equation Modeling (SEM) and Partial Least Squares (PLS) for data analysis, the research collected data from 100 accounting students in Surabaya who use pay later services, selected through purposive sampling. The results indicate that objective financial knowledge significantly influences confidence in managing finances, which subsequently has a significant effect on high-risk credit behaviors. However, objective financial knowledge does not have a direct impact on high-risk credit behaviors, and perceived financial knowledge does not influence either high-risk credit behaviors or confidence in managing finances. Additionally, confidence in managing finances does not mediate the relationship between either type of financial literacy and high-risk credit behaviors. This study underscores the importance of enhancing financial knowledge and self-confidence among accounting students to curb high-risk credit behaviors. The findings offer valuable insights for future research in this area and contribute to the development of theories related to planned behavior, financial knowledge, and confidence in managing finances in mitigating high-risk credit behaviors, particularly with the increasing use of pay later credit options.